2012
DOI: 10.1007/s00405-012-2264-4
|View full text |Cite
|
Sign up to set email alerts
|

Long term results in late implanted adolescent and adult CI recipients

Abstract: The aim of the present study is to assess long-term outcomes of CI in prelingual deafened adolescents and adults, describing, where present, differences in performance, self perceived benefit and highlighting specific characteristics. Twenty-three patients were enrolled: 10 adolescents, 13 young adults. Each patient underwent speech perception/language development, psychological evaluation and structured interviews on self perception concerning CI. 70 % adolescents and 100 % adults used their cochlear implant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
1
19
0
4
Order By: Relevance
“…High user satisfaction rates have consistently been reported in studies on early-deafened CI users, even in subjects with almost negligible gain in auditory performance [Bosco et al, 2013;Caposecco et al, 2012;Hinderink et al, 1995;Kaplan et al, 2003;Peasgood et al, 2003;Zwolan et al, 1996]. A number of studies have evaluated quality of life before and after implantation and found significant postoperative improvements, mainly in hearing-related quality of life questionnaires [Klop et al, 2007;Most et al, 2010;Schramm et al, 2002;Straatman et al, 2014;van Dijkhuizen et al, 2011], but also in hearingrelated domains of general health status questionnaires [Klop et al, 2007;Straatman et al, 2014].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…High user satisfaction rates have consistently been reported in studies on early-deafened CI users, even in subjects with almost negligible gain in auditory performance [Bosco et al, 2013;Caposecco et al, 2012;Hinderink et al, 1995;Kaplan et al, 2003;Peasgood et al, 2003;Zwolan et al, 1996]. A number of studies have evaluated quality of life before and after implantation and found significant postoperative improvements, mainly in hearing-related quality of life questionnaires [Klop et al, 2007;Most et al, 2010;Schramm et al, 2002;Straatman et al, 2014;van Dijkhuizen et al, 2011], but also in hearingrelated domains of general health status questionnaires [Klop et al, 2007;Straatman et al, 2014].…”
Section: Introductionmentioning
confidence: 97%
“…As speechcoding strategies evolved towards SPEAK, CIS and ACE from the late 90s onwards, studies showed that more beneficial results were possible for prelingually deafened adults [Schramm et al, 2002;Waltzman and Cohen, 1999;Waltzman et al, 2002]. A number of recent studies have demonstrated significant postoperative improvement in the mean scores of this group of CI users in various speech-understanding tests [Bosco et al, 2013;Caposecco et al, 2012;Klop et al, 2007;Rousset et al, 2016;Santarelli et al, 2008;Shpak et al, 2009;van Dijkhuizen et al, 2011;Yang et al, 2011]. Nevertheless, there are still large interindividual differences, with part of the early-deafened population obtaining scores slightly above or at 0% when speech understanding is assessed using open-set words or sentences.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one UK cochlear implant centre the partial or non-use rate was reported to be 15% (Emond et al, 2013). Under-use of the implant has also been reported in adolescents with monaural devices, even where hearing outcomes such as speech perception are good (Bosco et al, 2013 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, teenagers with pre-lingual deafness can receive benefit from a second cochlear implant, even if there has been more than 16 years between devices (Galvin et al, 2010). A recent study of a small sample of ten pre-and perilingually deafened (during the development of speech and language) teenagers showed a significant improvement in speech perception with benefits such as improved self-esteem and greater self-sufficiency, and high satisfaction with the device (Bosco et al, 2013).…”
Section: Pre-and Post-lingual Cochlear Implantationmentioning
confidence: 99%
“…Cochlear implantation is considered an elective choice for the treatment of severe and profound deafness [3] . Cochlear implantation also represents a valid option in post-lingually deafened adults, who manage to achieve high levels of speech perception not only in quiet but also in the presence of noise and when using the telephone [4] .…”
Section: Discussionmentioning
confidence: 99%